MANAJEMEN RISIKO BANK WAKAF MIKRO (BWM) DAN KEMUNGKINAN PENGEMBANGAN MODEL BERBASIS SYARIAH DI INDONESIA - Rasiam, Rasiam (Fakultas Syariah (Syari'ah Faculty ), 2025)
The purpose of this study is to analyze the risk of Micro Waqf Bank (BWM) in terms of legal and operational risks. This research method is descriptive with a qualitative approach. This type of research is a case study, namely the practice of Micro Waqf Banks in Indonesia. In addition, this study also examines the literature related to the legal basis of Micro Waqf Banks (BWM). Finding; First; Micro Waqf Banks (BWM) in Indonesia face legal risks that are very crucial and cannot be ignored. The existence of regulatory dualism regarding Micro Waqf Banks as Islamic Microfinance Institutions (LKMS) with cooperative legal entities, is regulated in Law Number 17 of 2012 concerning Cooperatives and Law Number 1 of 2013 concerning Microfinance Institutions. This dualism in the regulation of Micro Waqf Banks results in disharmony or overlapping of arrangements regarding establishment and licensing, guidance, supervision, inspection and evaluation. This dualism of the legal basis will definitely complicate the operational management of BWM going forward. Second; management risk lies in the small and less qualified human resources. The Islamic boarding schools that are entrusted with managing the revolving of BUMN CSR funds have not been optimally trained and have not had experience so far. Third; The models that allow it to be developed are syirkah and ijarah models. This model is more flexible and far more productive, in terms of sharia it is safe because it has been issued directly by the Indonesian Ulema Council (MUI). This means that the halal syirkah and ijrah products have received legality from the authorities.